Left versus right approach for middle and lower esophageal squamous cell carcinoma: A propensity score-matched study - Zhang, Xining; Qi, Kang; Huang, Weiming; Liu, Jingwei; Lin, Gang; Li, Jian (Frontiers in Oncology, 2022)
Background: There are concerns about the oncological efficacy of the left approach esophagectomy for middle and lower squamous esophageal carcinoma (ESCC) despite the superior short-term outcomes. A propensity score matched retrospective study was conducted to evaluate both the short- and long-term effects of the left approach. Methods: The data of patients with ESCC who underwent curative resection via either left or right approach between January 2010 and December 2015 was collected. Propensity score matching (PSM) was performed, and maximally selected rank statistics (MSRS) were utilized to determine the appropriate number of lymph nodes needed to be resected during esophagectomy. Results: One hundred and forty-eight ESCC patients received esophagectomy via the right approach, and 108 received the left approach esophagectomy. After PSM, the left approach esophagectomy showed statistically significant superiority in operative time, time to oral intake, and there was a trend of shorter length of hospital stay. Fewer cervical, upper thoracic and recurrent laryngeal nerve lymph nodes were harvested via the left approach than the right approach; the total number of lymph nodes harvested via the left and right approaches was similar. Similar long-term survival outcomes were reached. MSRS suggested that at least 25 and 27 lymph nodes are needed to be resected during esophagectomy for better survival for T1-2 and T3-T4a patients, respectively. Conclusions: The left approach esophagectomy could facilitate postoperative recovery for patients with middle and lower ESCC. Moreover, with adequate lymphadenectomy, the left approach esophagectomy could achieve similar long-term outcomes for middle and lower ESCC patients.